DIGITAL MARKETING MANAGEMENT VIA INSTAGRAM ACCOUNT @kedai.serenada - Nayla Maulidita; Salsha Amalia Azraa; Khansa Naura; Ketut Kurniasari, Ni Gusti Ayu (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
The rapid growth of coffee shops in various big cities reflects shifting lifestyle trends and increasing consumer demand for unique social spaces. This study aims to explore customer experiences and identify key factors influencing satisfaction levels during visits to Serenada Coffee Shop. Using a qualitative research approach, data were collected through in-depth interviews with both regular customers and first-time visitors. The findings reveal that customer satisfaction is shaped by a combination of several crucial aspects, including product quality, ambiance, service performance, pricing, and strategic location. These elements collectively contribute to creating a memorable and fulfilling customer experience. Moreover, interactions between customers and the coffee shop environment play an essential role in fostering loyalty and repeat visits. This research not only provides insights into the dynamics of customer behavior within the coffee shop industry but also offers practical guidance for business practitioners seeking to enhance service quality and customer engagement. A notable observation is the effective use of social media, particularly through the Instagram account @kedai.serenada, which functions as a digital platform to introduce coffee products, interact with customers, and strengthen the brand’s market presence. The study emphasizes the importance of integrating offline service excellence with online promotional strategies to maintain the long-term sustainability and visibility of Serenada Coffee Shop.